2020
DOI: 10.1515/ovs-2020-0101
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mastitis in Nigerian livestock: a Review

Abstract: Mastitis is a disease of livestock that directly impede livestock production and thus hindering the socio-ecological development of sub-Saharan Africa. Studies have estimated the prevalence of this disease in 30% of Africa countries, with Ethiopia having the highest prevalence. The coverage is low, despite the wide livestock and dairy farms distribution in Africa. Furthermore, estimated economic losses due to the impact of mastitis are lacking in Nigeria. The disease is endemic in Nigeria as indicated by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Figure 2: Boxplot showing the levels of somatic cell counts in samples by number of different bacteria species isolated from them renewed call for the use of SCC determination in mastitis monitoring (Adamu et al, 2020) that has been reported by only a few workers in Nigeria (Ahaotu et al, 2013;Olatoye et al, 2018). Apart from indicating mastitis presence and direct production losses, High SCC has been associated with milk of low quality that deteriorates easily.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2: Boxplot showing the levels of somatic cell counts in samples by number of different bacteria species isolated from them renewed call for the use of SCC determination in mastitis monitoring (Adamu et al, 2020) that has been reported by only a few workers in Nigeria (Ahaotu et al, 2013;Olatoye et al, 2018). Apart from indicating mastitis presence and direct production losses, High SCC has been associated with milk of low quality that deteriorates easily.…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing factors such as poor management, hygiene, teat injuries and faulty milking machines are known to play significant roles in the entry of the infectious agents and the course of the disease (Zenebe et al, 2014). In Nigeria, management and diseases particularly mastitis, constitute major constraints to effective dairy husbandry system (Shittu et al, 2008;Adamu et al, 2020). The economic impact of mastitis has been widely encountered by most livestock farmers; however, determining the actual cost is very challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The economic impact of mastitis has been widely encountered by most livestock farmers; however, determining the actual cost is very challenging. The economic loss due to mastitis at herd level can be classified into four main sources attributable to loss due to depreciation in the milk quality, reduced milk production especially in chronic sub-clinical infection, loss due to discarded milk, cost of veterinary services, and treatment, as well as losses incurred due to increase replacement rate or culling of cows during their productive years (Adamu et al, 2020). The primary aim of herd health programme is to minimize economic loss due to disease.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, several studies have reported the isolation of different bacteria from mastitis in ruminants with varying prevalence. However, most of these studies relied on the classical methods for the identification of the bacterial causes of mastitis [2].…”
Section: Introductionmentioning
confidence: 99%